2022
DOI: 10.3390/nano12040614
|View full text |Cite
|
Sign up to set email alerts
|

Comparable Studies on Nanoscale Antibacterial Polymer Coatings Based on Different Coating Procedures

Abstract: The antibacterial activity of different antibiotic and metal-free thin polymer coatings was investigated. The films comprised quaternary ammonium compounds (QAC) based on a vinyl benzyl chloride (VBC) building block. Two monomeric QAC of different alkyl chain lengths were prepared, and then polymerized by two different polymerization processes to apply them onto Ti surfaces. At first, the polymeric layer was generated directly on the surface by atom transfer radical polymerization (ATRP). For comparison purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Indeed, it should be remarked that other approaches can be applied to form novel coatings in order to protect materials from corrosion, bacterial activity, and solvent impact, etc. Experiments and mathematical models have been shown in recently published papers [34][35][36][37][38][39][40][41][42][43] and have demonstrated their various advantages. However, the LOD technique has certain unique advantage that allows treatment of all types of the materials, such as inorganic crystals, semiconductors, metals, and some high-temperature polyimide structures, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it should be remarked that other approaches can be applied to form novel coatings in order to protect materials from corrosion, bacterial activity, and solvent impact, etc. Experiments and mathematical models have been shown in recently published papers [34][35][36][37][38][39][40][41][42][43] and have demonstrated their various advantages. However, the LOD technique has certain unique advantage that allows treatment of all types of the materials, such as inorganic crystals, semiconductors, metals, and some high-temperature polyimide structures, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The original articles include studies on the potential applications of the investigated antibacterial nanostructures and examine different uses, such as devices in the healthcare sector [10], suture materials [11], food packaging films [12], water treatment membranes [13], titanium-based alloys for medical implants [14], and tissue engineering scaffolds [15].…”
Section: Introductionmentioning
confidence: 99%
“…Their coatings showed good substrate adhesion, cytocompatibility under in vitro conditions, and good antimicrobial activity depending on the length of the alkyl chain of the quaternary ammonium compounds. Possible applications include equipment of metallic devices used in healthcare and medical implants [10]. Basov et al found that, after the application of the freeze/thaw method, the antibacterial activity of suture materials with Ag nanoparticles (AgNPs) was significantly higher than before their treatment with cyclic freezing.…”
Section: Introductionmentioning
confidence: 99%